2016
DOI: 10.1111/ajag.12353
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review of medical assessment units and older people with complex health needs

Abstract: Findings from this review indicate that future policy, research and practice relating to MAUs should focus on older people with complex needs, patient-centred metrics and those MAU characteristics most likely to deliver positive health outcomes to this particular cohort of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The delivery of care on in our study was similar to other MAPUs and patient discharges occurred within 48‐72 hours . The regulated timeline to provide patient care in this setting highlights the need for nurses to maximise each opportunity to connect and develop a relationship with patients and their family .…”
Section: Discussionsupporting
confidence: 52%
“…The delivery of care on in our study was similar to other MAPUs and patient discharges occurred within 48‐72 hours . The regulated timeline to provide patient care in this setting highlights the need for nurses to maximise each opportunity to connect and develop a relationship with patients and their family .…”
Section: Discussionsupporting
confidence: 52%
“…The traditional model of acute medical care often involves hospital admission. To address the high level of bed occupancy, different entries for acute patients have emerged facilitating more flexible and dynamic bed management [6] with a proliferation of observation and assessment units [7, 8]. These entries comprise a wide variety of forms and allow patients to be observed on a short-term basis without using inpatient facilities [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…This integrative review identified 42 papers reporting 41 studies that examined technology in relation to the quality of nursing work in acute hospital settings. The focus of this review was to describe the research methods used in these studies, thereby addressing a current gap often “neglected” in integrative literature reviews (Rushton et al, ). Understanding how nursing work is defined and measured and how its outcomes are evaluated is essential to recognise and measure how emerging technologies contribute to, or hinder, quality nursing care in complex acute settings.…”
Section: Discussionmentioning
confidence: 99%